2002
DOI: 10.1093/nar/gnf067
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of mitochondrial DNA deletions in individual cells by real-time PCR

Abstract: Defects of mitochondrial DNA (mtDNA) are an important cause of disease and play a role in the ageing process. There are multiple copies of the mitochondrial genome in a single cell. In many patients with acquired or inherited mtDNA mutations, there exists a mixture of mutated and wild type genomes (termed heteroplasmy) within individual cells. As a biochemical and clinical defect is only observed when there are high levels of mutated mtDNA, a crucial investigation is to determine the level of heteroplasmic mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
235
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 296 publications
(248 citation statements)
references
References 33 publications
10
235
0
3
Order By: Relevance
“…Accordingly, we have shown that deletion level increases with higher degrees of OXPHOS deficiency across a total of 673 fibers from 6 patients. Whereas the deletion level recorded in deficient fibers was consistently high among all patients (>85%), the mean deletion level recorded in 236 respiratory‐normal fibers was 22.6% (SD = 23.4%), consistent with others studies recording an average deletion level of 21 to 31% 9, 12, 13. The variable deletion levels of the respiratory‐normal fiber groups recorded in the 6 patients reported here (and others in previous studies) reflect their different homogenate mtDNA deletion levels.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Accordingly, we have shown that deletion level increases with higher degrees of OXPHOS deficiency across a total of 673 fibers from 6 patients. Whereas the deletion level recorded in deficient fibers was consistently high among all patients (>85%), the mean deletion level recorded in 236 respiratory‐normal fibers was 22.6% (SD = 23.4%), consistent with others studies recording an average deletion level of 21 to 31% 9, 12, 13. The variable deletion levels of the respiratory‐normal fiber groups recorded in the 6 patients reported here (and others in previous studies) reflect their different homogenate mtDNA deletion levels.…”
Section: Discussionsupporting
confidence: 90%
“…Fibers positive for both complex I and complex IV immunoreactivity (OXPHOS group 1), deemed respiratory‐”normal,” harbored variable deletion loads, as previously reported 9. In contrast, fibers classed as negative for both complex I and complex IV consistently showed the highest mtDNA deletion levels, with a notably narrow range of deletion level (see Table 2).…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…Several methods have been used previously to quantify the level of mtDNA 4977 mutation. Long range PCR, primer-shift PCR and semi-quantitative PCR are time-consuming and the results are sometimes not reproducible (18)(19)(20). Furthermore, these PCR methods use an endpoint determination that may not be truly quantitative because of plateau effects (21).…”
Section: Discussionmentioning
confidence: 99%